Somatosensory temporal discrimination in patients with primary focal dystonia. Issue 12 (18th June 2009) - Scontrini, A; Conte, A; Defazio, G; Fiorio, M; Fabbrini, G; Suppa, A; Tinazzi, M; Berardelli, A
Abstract : Purposes: To determine whether somatosensory temporal discrimination will reliably detect subclinical sensory impairment in patients with various forms of primary focal dystonia. Methods: The somatosensory temporal discrimination threshold (STDT) was tested in 82 outpatients affected by cranial, cervical, laryngeal and hand dystonia. Results were compared with those for 61 healthy subjects and 26 patients with hemifacial spasm, a non-dystonic disorder. STDT was tested by delivering paired stimuli starting with an interstimulus interval of 0 ms followed by a progressively increasing interstimulus interval. Results: STDT was abnormal in all the different forms of primary focal dystonias in all three body regions (eye, hand and neck), regardless of the distribution and severity of motor symptoms. Receiver operating characteristic curve analysis calculated in the three body regions yielded high diagnostic sensitivity and specificity for STDT abnormalities. Conclusions: These results provide definitive evidence that STDT abnormalities are a generalised feature of patients with primary focal dystonias and are a valid tool for screening subclinical sensory abnormalities.